The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2176/nmc.53.409
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Coiling as the First Treatment Strategy for Ruptured Pericallosal Artery Aneurysms: Results, Complications, and Follow Up

Abstract: We apply endovascular coiling as the first treatment option for ruptured pericallosal artery aneurysms. We conducted a retrospective analysis of the clinical and radiological outcomes of this treatment strategy and morphological factors associated with the success of endovascular coiling, to assess the safety and feasibility of our management strategy. From January 2003 to January 2012, we attempted endovascular coiling as the first-intention treatment for 30 consecutive patients with ruptured pericallosal art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…The previous studies have shown that the Hunt and Hess grade at admission, intracerebral hemorrhage, intraventricular hemorrhage, severe preoperative hydrocephalus, age, and rebleeding before treatment were significant predictors of poor clinical outcomes in patients undergoing either endovascular or microsurgical treatment of distal ACA aneurysms. [ 1 , 16 , 24 ] In univariate analysis, age and hydrocephalus showed significant differences; however, no significant differences were found in multivariate analysis. This may be due to the small number of cases.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The previous studies have shown that the Hunt and Hess grade at admission, intracerebral hemorrhage, intraventricular hemorrhage, severe preoperative hydrocephalus, age, and rebleeding before treatment were significant predictors of poor clinical outcomes in patients undergoing either endovascular or microsurgical treatment of distal ACA aneurysms. [ 1 , 16 , 24 ] In univariate analysis, age and hydrocephalus showed significant differences; however, no significant differences were found in multivariate analysis. This may be due to the small number of cases.…”
Section: Discussionmentioning
confidence: 87%
“…[ 7 ] Since then, several authors have reported high technical success rates, high complete occlusion rates, and good neurological outcomes. [ 4 , 7 , 15 , 16 , 22 , 24 ] Conversely, Pierot et al . described endovascular management of eight cases of distal ACA aneurysms in 1996; coil embolization was successful in only 25% cases.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, endovascular coiling provides a high rate of CO-similar to that achieved with surgical clipping-with improved outcomes gradually Table 4 Characteristics, outcome, and mortality/morbidity rates from six endovascular series and our DAC aneurysm cases Unless otherwise stated, the results are given as the number (%). CO: complete obliteration; DAC: distal access catheter; N/A: not available; RN: residual neck increasing 2, [14][15][16][17][18] (Table 4). Comparing five surgical clipping studies 2,7-10) ( Table 3) with seven endovascular coiling studies including our experiments 2, [14][15][16][17][18] (Table 4), the ratio of ruptured aneurysm and HH grade 4-5 are almost equal, although the total number of surgical clipping patients is 1.5 times that of endovascular coiling.…”
Section: Discussionmentioning
confidence: 99%
“…CO: complete obliteration; DAC: distal access catheter; N/A: not available; RN: residual neck increasing 2, [14][15][16][17][18] (Table 4). Comparing five surgical clipping studies 2,7-10) ( Table 3) with seven endovascular coiling studies including our experiments 2, [14][15][16][17][18] (Table 4), the ratio of ruptured aneurysm and HH grade 4-5 are almost equal, although the total number of surgical clipping patients is 1.5 times that of endovascular coiling. Our outcomes showed a slightly lower rate of CO/RN, although there were few complications and little re-bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these reports and the fact that previous reports included unruptured cases, whereas we did not, we believe that our intraprocedural rupture rate is not excessive. It is well known PA aneurysms are smaller than non-PA aneurysms tend and that they tend to rupture at a smaller size 10 13 27) . In a study of a large number of aneurysm cases, the average diameter of ruptured aneurysms was reported to be 8.2 mm 8) , whereas the average aneurysm diameter in our patients was 5.0 mm.…”
Section: Discussionmentioning
confidence: 99%